Private Voluntary Health Insurance : Consumer Protection and Prudential Regulation - Brunner, Greg; Gottret, Pablo; Hansl, Birgit; Kalavakonda, Vijayasekar; Nagpal, Somil; Tapay, Nicole (Washington, DC: World Bank, 2013)
Health care expenditures can be financed through a mix of public resources and private spending. Private spending is a much larger share of total health spending in low- and middle-income countries than in higher income countries. Moreover, a significant percentage of private spending in those countries is out-of-pocket direct payments for health care services by individuals. Out of pocket expenditures account for more than 60 percent of the total health care spending in low-income countries and 40 percent of total health care spending in middle-income countries. A growing number of low- and middle-income governments are considering private health insurance as a way of both reducing the risk that individuals will have a catastrophic financial burden and achieving other public health care goals. Among these goals are reducing the financial burden on overstretched public health financing, achieving more equitable access to health care, and improving quality and efficiency in the delivery of health care services. An important component of a successful private health insurance market, however, is its legal framework. As discussed in detail later in this book, countries regulate insurance companies to counter systemic market failures that lead to an inefficient and inequitable market. In particular, insurance laws are designed to prevent insurers from becoming insolvent and from engaging in unfair practices and discriminatory behavior. When private health insurance serves as a significant source of financing in a nation's health care system, usually insurance laws also include a range of consumer protection laws that enhance both access to the services covered by private health insurers and the adequacy of the benefits provided by the insurer. This chapter provides a general overview of private health insurance. It begins with a discussion of the definition of private health insurance and the potential roles of private health insurance as part of a nation's health care financing system. In addition, the chapter reviews the variety of entities that sell private health insurance.